Work Life Balance Pada Working Mom: Peran Health Behavior dan Work Flexibility dengan Stress Management Sebagai Mediator: Penelitian - RA. Annisa Istiqomah; Yunita Faela Nisa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the influence of health behavior and work flexibility on work-life balance, with stress management as a mediating variable among working mothers who are micro-entrepreneurs (UMKM) in Serang City. The research employed a quantitative correlational approach using path analysis techniques. A total of 202 working mothers participated in the study, all of whom have children under the age of three and are actively running micro-enterprises in the Serang area. The findings indicate that both health behavior and work flexibility have significant effects on work-life balance, both directly and indirectly through stress management. These results highlight the importance of promoting healthy lifestyle behaviors, supporting flexible work policies, and strengthening stress management strategies to enhance the work-life balance of working mothers.